Incidence of Maxillary Midline Diastema in Iraqi Students in Baghdad City - Hamad, Nail Hasan (Al Mustansiriyah Journal of Pharmaceutical Sciences, 2015)
Maxillary midline diastema is one of important numerical anomalies of teeth which character as an open space between the maxillary central incisors so that many studies have been carried out in different countries of the world to find the prevalence of maxillary midline diastema. The purpose of this study was to determine the prevalence of the maxillary midline diastema and assess the gender difference in a selective sample of college and institute Iraqi student age (18-22) year in Baghdad city. A total sample of (1460) students distributed into (680) males and (780) females. The statistical analysis shows the incidence of maxillary midline diastema is (55) cases in the total sample with percent (3.8%) which is in males (3.4%) and (4.1%) in female. So it is found in females more than in males, the maxillary Midline Diastema.